IbPE KERAJINAN KERAMIK DAERAH PUNDONG DAN KASIHAN, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Hendri, Zulfi; Arianingrum, Retno; Widarto, - (Universitas Negeri Yogyakarta, 2015)
The long term goal of the program's science and technology for ExportProducts (IbPE) is to increase the productivity of ceramics in Small and MediumEnterprises Industries (SMI)